Chemical burn following 50% trichloroacetic acid for acne: Presentation of a case and a focused review - Hannah Liu; Amor Khachemoune; Rashid M. Rashid (Wolters Kluwer Medknow Publications, 2016)
Background: Chemical peels are widely used minimally invasive procedures with both cosmetic and medical indications. Although known for their general safety and efficacy, peels can rarely result in significant complications. Objective: Here we report the first case in the peer-reviewed literature of chemical burn from erroneous home use of 50% trichloroacetic acid. Methods: A focused literature review was performed of complications relating to chemical peels. Results: Chemical burns from trichloroacetic acid peels are rare. To our knowledge, this is the first such case reported with supporting histopathological data. Conclusions: Physicians must be aware of the potential complications of chemical peels, prevention strategies, and treatment modalities.